Dissolution and precipitation of air in dissolved air flotation - Steinbach, Sandra (2012)
D.Ing. === The use of dissolved air flotation (DAF) as a water clarification process has gained momentum over the past two decades. Despite its increased application there is a lack of information concerning the understanding of the underlying principles of the process. Plants are being designed based mainly on empirical guidelines, especially with respect to the bubble production system. Bubbles are generated in the DAF process when water, supersaturated with air under pressure, is released under atmospheric conditions. The efficiency of air dissolution and precipitation determines the quantity of air available for flotation and thus, to a large extent, the success of the whole DAF process. The first part of this thesis deals with a rational model for predicting the air transfer efficiency in packed saturators which are used in most modern DAF plants to dissolve air into water. The model assumes the Lewis-Whitman two-film theory for interfacial mass transfer and uses the Onda correlations to estimate the mass transfer coefficient. The model provides good insight into the effects of key design parameters on the air transfer efficiency. The experimental verification of the model required a method for predicting the saturator air composition and a technique to practically determine the air transfer efficiency in the packed bed of an operating saturator. Both methods are described in detail in this study. The verification of the mass transfer model showed a close agreement of experimental and theoretical results and the model thus provides a powerful tool for the design of packed saturators. The second part of the thesis deals with air precipitation and the quantity of air released after depressurization. Based on a literature review on this subject it was assumed that the air release is incomplete and that it would be a function of the operating conditions of the saturation system as well as of the design of the injection nozzle across which the pressure is released. Since the injection nozzles play an important role in the DAF process numerous experiments were carried out which measured the released air volume for different nozzle configurations and saturator pressures. The results of this study showed that the air release after depressurization is indeed incomplete and that it takes a long time for all the excess air to come out of solution. It was found that the efficiency with which the air was released is a function of the saturator pressure and the nozzle design. The experimental observations led to the formulation of a two-step air release model, which explains the precipitation process in terms of a slow and fast release step. The mathematical framework for quantification of the model is provided. Once the model is quantified it will be possible to compare the performance of different injection nozzles solely with regard to their design features and independent of any parameters influencing the air release downstream of the nozzle. This model may then help to further the understanding of the precipitation process and could lead to the development of some rational guidelines for nozzle design and prediction of nozzle performance.